Hospital-based analysis of eye diseases at Karitas Hospital, Southwest Sumba, 2015 (Medical Journal of Indonesia, 2018)
Background: This study aimed to determine the profile of eye diseases at Karitas Hospital in Southwest Sumba during 2015.Methods: The cross-sectional and descriptive study was conducted by analyzing medical records of 1706 patients who presented with eye complaints at Karitas Hospital, Southwest Sumba, in 2015. Complete medical records were recovered from 1363 patients, who served as subjects for this study. Results: Thirty-six percent of subjects were elderly (>55 years old) and 9.9% were children (<18 years old). Female patients comprised 56.4% of the study population and males 43.6%. Non-infectious eye diseases dominated (89.8%; 95%CI: 88.2%–91.4%) compared to infectious diseases (8.2%; 95%CI: 6.7%–9.7%) and mixed cases (2%; 95%CI: 1.3%–2.7%). Avoidable causes of blindness, cataract (34%), and refractive error (17.3%), were mostly found among non-infectious cases, while conjunctivitis (52.7%) and keratitis (17%) were the most commonly encountered infectious diseases. Conclusion: Eye diseases at Karitas Hospital in Southwest Sumba mostly comprised non-infectious diseases. The most commonly noted non-infectious diseases were cataracts and refractive errors, while conjunctivitis and keratitis were the most commonly found infectious diseases. Due to the high amount of patients seeking eye care within Southwest Sumba, ophthalmologists and proper equipment are needed at the Karitas Hospital.